Productive performance and carcass composition of male lambs (Ovis aries) in Pérez Zeledón, Costa Rica - Navarro García, Arturo (2019)
The aim of this study was to evaluate the productive performance and carcass composition in heavy lambs, developed in Pérez Zeledón, Costa Rica. Eleven castrated lambs were fed with the same type and doses of forage and supplemented with concentrates.  The weight of the lambs was recorded from birth to 10 months of age approximately.  The lambs were harvested and the weights of the carcasses were recorded.  Morphological measurements such as carcass length, breast width, length and perimeter of leg, ribeye area and backfat thickness were made in the Longissimus dorsi muscle.  The lambs evaluated had an average birth weight of 2.7 kg, with average daily weight gains of 163 g and 49.27 kg at 302 days at average age.The average live weight at the slaughterhouse was 48.0 kg and for the hot carcasses (CC) and cold carcasses (CF) were 21.15 kg and 20.79 kg respectively.  The carcass yield was 44.04% when there wasn’t drip loss. The compactness indexes were 0.71 for the leg and 0.33 for the carcass. Drip loss reached values of 1.7%. For the tissue composition, an average of 15.47 kg of muscle, 3.19 kg of bone and 1.85 kg of fat were obtained, with a muscle/bone ratio of 4.93 and muscle/fat of 8.50.  The cuts of the loin represented 15.4% of the total muscle, the leg 28.3%, the front quarter 31.0% and the flank + rib 25.3%.  Non-marketable products accounted for 47.1% of the live weight; from these, 4.8% corresponded to the head, 2.2% to the legs, 12.6% to the hide and wool, 2.0% to the viscera and 25.4% to the gastrointestinal tract (TGI).